NEWSPAPERS/WIRE SERVICES. - Neuts, Dana (Quill)
The article identifies the news stories that appeared in newspapers and wire services that have been honored with the 2011 Sigma Delta Chi Awards. The "Chicago Tribune" covered the worst blizzard that struck Chicago, Illinois in at least a decade. "Valley News" was honored for its coverage of the devastation brought about by Tropical Storm Irene. Matt Lakin of the "Knoxville News Sentinel" reported on the dangers of prescription drug addiction.